Study of Four (4) Semi-Empirical Models for Estimating Direct Radiation from the Sun and Modeling for Application to the Solar Thermodynamic System - SANI DAN NOMAO, Harouna; BOUBACAR MAIKANO, Abdoulaye; SIDO, Mariama P.; BOUKAR, Makinta; MADOUGOU, Saïdou (European Journal of Applied Sciences, 2022)
Concentrated solar power refers to all techniques aimed at transforming the energy of solar radiation into heat and converting it into electrical energy through a thermodynamic cycle. This sector is mainly advantageous for countries with a lot of sunshine, such as Niger. In opposition to photovoltaic solar technology which uses global radiation, thermodynamic solar technology uses direct radiation from the sun. To evaluate direct radiation, our study focuses on four semi-empirical models: Perin-Brichamlbault, Liu_Jordan, Kasten, and R_sun model. Our work focuses on the comparison of direct solar radiation results obtained experimentally with these semi-empirical models and the modeling of direct radiation. The measurements of direct solar radiation were compared with those of semi-empirical models. This comparison allowed us to identify the semi-empirical model that is closest to experimental results with an average relative error of 9.80%: it’s Perrin, followed by R_sun 15.11%, Liu_Jordan 18.26%, and Kasten model 31.69%. We have adapted the Perin-Brichamlbault model by adding two parameters: solar constant and correction Earth-Sun distance. By using these parameters average relative error was reduced to 4.93% over the day and instantaneous errors to around 1% between 9 am and 4 pm. That corrected Perin-Brichamlbault model can be considered one of best for the prediction of solar thermodynamic systems.